The effect of nature-based landscape design on human health and well-being: a thematic synthesis - Zhu, Qiuxia; Yao, Pinyi; Li, Jiexu (Journal of Environmental Engineering and Landscape Management, 2025)
Population growth, high-density living situations, and rapid urbanization lead to environmental change that affects ecosystems, human behavior, and well-being. To design health-promoting urban landscapes, it is necessary to conduct more detailed studies of landscape features. However, there is a lack of review articles discussing specific approaches and factors of landscape design for human well-being in evidence-based landscape research. Therefore, this review aims to explore the research trends and future studies’ direction by adopting a thematic analysis approach. Using ATLAS.ti 23 software, we analyzed 40 literature articles on landscape design and human well-being published between 2018 and 2022. The article attribute findings show the research trends on the topic. Six main themes emerged from the subsequent qualitative analysis: (1) Human-nature Interactions, (2) Health-promoting Design, (3) Integrative Strategies, (4) Landscape Intervention, (5) Perceptions and Restorativeness, and (6) Sustainability. The resulting framework serves to guide landscape designers, urban planners, and researchers to improve the effectiveness of public social, physical, and mental health with feasible measures and design approaches.